2014
DOI: 10.1177/0957650914558166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foam structure and material on the performance of premixed porous ceramic burner

Abstract: An experimental setup was developed to investigate the physical characteristics of ceramic foam, used in reaction layer, on the performance of a porous burner. This premixed burner included mainly four sections: premixed, preheating, combustion zone and an integrated heat exchanger. The objective of this work was to investigate effects of different kinds of ceramic foams with various porosity, pore density and materials on the burner performance. The combustor was operated with natural gas and diverse structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Effects of the material and shape of the porous media on the flame dynamics and pollutant emissions were studied by several researchers. 810 Results suggested that solid matrix had an effective role on flame situation and pollutant formation controlling. Experimental study examining the influence of solid structure on the performance of the premixed methane–air combustion in a two-layer porous burner showed that the flame stability limit as well as flame peak temperature were enhanced by increasing the diameter of the alumina pellets.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of the material and shape of the porous media on the flame dynamics and pollutant emissions were studied by several researchers. 810 Results suggested that solid matrix had an effective role on flame situation and pollutant formation controlling. Experimental study examining the influence of solid structure on the performance of the premixed methane–air combustion in a two-layer porous burner showed that the flame stability limit as well as flame peak temperature were enhanced by increasing the diameter of the alumina pellets.…”
Section: Introductionmentioning
confidence: 99%
“…In more recent studies, Keramiotis, Stelzner and Trimis (2012) performed a comprehensive experimental study to investigate thermal efficacy, pollutant emissions and stable operating range of a porous burner for methane and LPG. Shakiba et al (2015) experimentally investigated the effects of foam properties on the porous burner performance. Experiments are conducted for different materials, pore densities and porosities.…”
Section: Introductionmentioning
confidence: 99%
“…Various experimental and numerical investigations examined the effects of geometrical and thermophysical properties of porous matrix on flame characteristics in the porous burner. 1924…”
Section: Introductionmentioning
confidence: 99%